Listeria spp. in Street-Vended Ready-to-Eat Foods - Moustafa El-Shenawy; Mohamed El-Shenawy; Jordi Mañes; Jose M. Soriano (Interdisciplinary Perspectives on Infectious Diseases)
Street-vended ready-to-eat food sold in Egypt, including sandwiches and dishes of traditional food, was examined for the presence of Listeria species. Out of 576 samples, 24% were found to contain Listeria species. L. monocytogenes and L. innocua were isolated from 57% and 39% of the contaminated samples, respectively. Other Listeria spp. were detected with lower frequency. L. monocytogenes of ≥103 CFU/g were detected in 7% of the total examined samples, which represent 49% of the contaminated food samples (meat, poultry, seafood, dairy products, and products of plant origin). Most of the samples contaminated by L. monocytogenes had high levels of total viable bacterial counts. The results obtained may help to clarify the epidemiology of listeriosis in the country and draw the attention of the decision makers to issue hygienic regulations for food processing industries as well as street vendors in order to ensure safe street-vended ready-to-eat food.